Passerini multicomponent reaction: a versatile synthesis of nanomedicines for triple negative breast cancer treatment - Travanut, Alessandra (2021)
The Passerini three component reaction (Passerini-3CR) is a multicomponent isocyanide-based reaction, which combines in one-pot and in a straightforward way an aldehyde, an isocyanide and a carboxylic acid into an ester-amide product. The flexibility of the reaction combined with the accessible functionality and the inherent biodegradability of the polymer product therefore offers much potential for new materials applicable in drug delivery and medicinal chemistry. In particular, the high functional group content in the Passerini polymer backbone could be of value in cancer drug delivery systems, as many materials designed for oncology applications lack sufficient drug payload. In this thesis, the focus is on materials for Triple Negative Breast Cancer (TNBC) therapies, as TNBC is an aggressive subtype of breast cancer that has poor patient survival and lack of targeted therapies. Patients are currently treated with taxane or anthracycline-based chemotherapy regiments, which have positive clinical outcomes only in the 30-40% of patients in early stage and poor survival in metastatic patients. The work in this study aims to develop functional biodegradable and biocompatible drug delivery systems for the chemotherapy treatment of TNBC, by exploiting the versatility of the Passerini-3CR. In Chapter 2, amphiphilic diblock copolymers with mPEG 2 and 5 kDa were synthesized via Passerini-3CR and formulated into polymersomes. The vesicles had a colloidally-stabilising and anti-biofouling PEG shell, were found to be stable in blood-mimicking pH conditions and to have low critical aggregation concentrations. The cytocompatibility of Passerini copolymers was verified in TNBC cells and non-cancerous human mammary epithelial cells. The internalization of fluorescently labelled Passerini polymersomes was investigated in 2D and 3D in TNBC cells and was found to be concentration dependent and endocytosis mediated. Doxorubicin was loaded in the polymersomes via the remote transmembrane pH gradient method. The efficacy of the doxorubicin-loaded polymersomes was found to be comparable with the free drug, thus indicating efficient release of doxorubicin from the delivery system. Furthermore, the drug was found to be selectively released under endolysosomal mimicking pH acidic conditions and retained under blood mimicking pH conditions. In Chapter 3, amphiphilic triblock copolymers were synthesized via Passerini-3CR and decorated on the surface with the cMET binding peptide as a targeting agent. The cMET receptor has been reported to be overexpressed in TNBC, therefore the polymersomes decoration with the cMET binding peptide was aimed to improve the actively targeted polymersomes internalization in TNBC cells over non-cancerous cells. Uptake studies were performed in TNBC cells in 2D and 3D culture, and the actively targeted polymersomes were found to be internalized to a higher extent than the untargeted analogues. Finally, in Chapter 4, the versatility of the Passerini-3CR was exploited for the synthesis of diblock amphiphilic copolymers with a high density of alkene pendant groups. These groups were oxidised by ozonolysis into aldehydes, which were quantitatively conjugated to the amino group of doxorubicin via the pH-responsive amine linker. The obtained doxorubicin-polymer conjugates were assembled into solid nanoparticles and tested in TNBC cells. The prodrug nanoparticle was found to be more cytotoxic than the free drug, suggesting the potential of this formulation of improving the doxorubicin activity, by performing a constant and continuous drug release in the endolysosomal cellular compartment. Moreover, the drug was found to be selectively released under endolysosomal mimicking pH conditions and to be retained under blood pH mimicking conditions. Overall, these results demonstrate that the Passerini-3CR is a promising synthetic route to generate polymeric nanomedicines that might in future improve the chemotherapy treatment of TNBC.